Grape seed polyphenol extract and cognitive function in healthy young adults: a randomised, placebo-controlled, parallel-groups acute-on-chronic trial. (2nd January 2022) - Bell, Lynne; Whyte, Adrian R.; Lamport, Daniel J.; Spencer, Jeremy P. E.; Butler, Laurie T.; Williams, Claire M.
ABSTRACT: Grapes are polyphenol-rich, and grape juice intake has shown cognitive benefits in middle-aged females and older adults with mild cognitive impairment. Extracts obtained from grape seeds have similarly been associated with cognitive benefits in older adults. The aim of this research was to investigate whether a highly purified grape seed-derived polyphenol extract was associated with cognitive benefits in healthy young adults following a single acute dose, and chronically following repeated daily dosage over 12 weeks. Following an acute-on-chronic, parallel groups, randomised, double-blind, placebo-controlled design, sixty adults aged 18-30 consumed either a 400 mg grape seed polyphenol extract (GSPE, n = 30) or a placebo ( n = 30). Cognitive function was assessed acutely at baseline and 2, 4 and 6 h post consumption, and chronically at 6 and 12 twelve weeks with a computerised battery of multiple cognitive tests. Mood was assessed with the Positive and Negative Affect Schedule. Linear marginal model analysis with baseline included as a covariate did not reveal a consistent pattern of cognitive benefits following the GSPE relative to the placebo either acutely or chronically when considering all outcome measures. GSPE was associated with some improvements in reaction time (acutely) and psychomotor skill (chronically), however the placebo was also associated with some benefits to reaction time and memory. Therefore, a 400 mg GSPE did not consistently improve cognitive function in healthy young adults. These findings suggest that younger, healthy populations are perhaps less sensitive to polyphenol extract doses <400mg relative to older, or cognitively compromised populations.